IMPLEMENTATION OF OJK’S GOOD CORPORATE GOVERNANCE GUIDELINES IN ISLAMIC FINANCIAL INSTITUTIONS: COMPLIANCE AND CHALLENGES - Selvie Anggraeni Noer (GREET, 2025)
This research critically investigates the implementation of the Financial Services Authority’s (OJK) Good Corporate Governance (GCG) guidelines in Indonesia’s Islamic financial institutions (IFIs), with a focus on compliance outcomes, operational challenges, and the interplay between Shariah governance and conventional regulatory frameworks. The study addresses a critical gap in prior research, which has often treated Shariah compliance and GCG as separate domains, by examining their integration in a single governance model. A mixed-methods approach was employed, combining semi-structured interviews with executives and Shariah Supervisory Board members, structured surveys quantifying adherence levels, and document analysis of governance policies and annual reports. Findings reveal a sector-wide compliance rate of 75%, with larger IFIs—such as Bank Syariah Indonesia—achieving above 80% compliance due to more mature governance infrastructures, while smaller IFIs remain at approximately 60% due to resource and expertise limitations. The research identifies internal barriers, including limited GCG awareness among staff and inadequate training, as well as external pressures such as complex regulatory demands and competitive market dynamics. The novelty of this study lies in its sector-wide empirical assessment that bridges theoretical governance models with real-world operational realities, offering granular insights into the structural, cultural, and regulatory factors that shape GCG effectiveness in IFIs. The findings hold significant implications for policymakers, regulators, and industry practitioners seeking to design targeted interventions that enhance governance quality, ensure Shariah-compliant ethical standards, and promote sustainable growth in the Islamic finance sector.